Synthesis, characterization and encapsulation studies of mixed diorganotin dithiocarbamates complexes / Nordiyana Zaldi - Nordiyana , Zaldi (2018)
Organotin and dithiocarbamate compounds are well-known anticancer agents and exhibit cytotoxic activities such as antiproliferative and antitumour. This research focused on the synthesis, characterization, and formulation studies of diorganotin(IV) dithiocarbamate complexes to identify their potential on anticancer properties. A total of ten mixed diorganotin(IV) dithiocarbamates complexes were successfully synthesized by the reaction of dithiocarbamate ligand with dimethyltin(IV) dichloride. The complexes were characterized by Fourier Transform Infrared (FT-IR), Nuclear Magnetic Resonance (NMR), and Ultraviolet-visible (UV‐Vis) absorption spectroscopy as well as Carbon, Hydrogen, Nitrogen, and Sulphur (CHNS) elemental analysis. The molecular structure of dimethyltin(IV) bis(morpholinodithiocarbamate) was determined by X-ray crystallography, showing a skew-trapezoidal bipyramidal coordination geometry. The dithiocarbamate ligands and its corresponding organotin complexes later then evaluated for their in vitro cytotoxic activity against several cancer cell lines such as the human lung carcinoma cell line (A549), human prostate cancer cell line (PC-3), and human breast cancer cell line (MCF-7). The compounds were screened using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) cytotoxicity assay. Most of the diorganotin(IV) complexes showed great cytotoxic activity compared to the dithiocarbamate ligand itself for MCF-7 cell line. The dimethyltin(IV)chloride N,N-diethyldithiocarbamate (C7) was subsequently encapsulated in vesicles and its drug release profile was studied in phosphate buffered saline (PBS) at pH 7.4. The C7 was selected because it has the lowest IC50 value against MCF-7 cell line as well as lower than the IC50 value for cisplatin. The drug formulation (vesicles) was prepared by thin film hydration method. The formulated vesicles loaded with C7 were further characterized for its percentage encapsulation efficiency, particle size, morphology, and release rate. The encapsulation efficiency was found to be high at more than 90%. Dynamic Light Scattering (DLS) was used to measure the particle size distribution. The results showed a size distribution of 119 nm with 100% intensity of vesicles loaded with C7. Field Emission Scanning Electron Microscopy (FESEM) was utilized for morphological analysis. The image showed an oblate shape vesicle with encapsulated C7. The complex was released from the vesicles up to 58% of the total loaded drug in two months. Based on the biological tests results and formulation outcomes, it can be concluded that diorganotin(IV) dithiocarbamate has a great potential in the pharmaceutical field for breast cancer therapies.